2017
DOI: 10.3389/fpls.2017.00542
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Comparative Transcriptomic, Metabolomic, and Anatomical Analyses of Two Key Domestication Traits: Pod Dehiscence and Seed Dormancy in Pea (Pisum sp.)

Abstract: The origin of the agriculture was one of the turning points in human history, and a central part of this was the evolution of new plant forms, domesticated crops. Seed dispersal and germination are two key traits which have been selected to facilitate cultivation and harvesting of crops. The objective of this study was to analyze anatomical structure of seed coat and pod, identify metabolic compounds associated with water-impermeable seed coat and differentially expressed genes involved in pea seed dormancy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
129
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(145 citation statements)
references
References 165 publications
11
129
0
Order By: Relevance
“…Significant changes in gene expression are marked with thicker lines. Enzyme names are abbreviated as follows: PAL phenylalanine ammonia-lyase, C4H cinnamate-4-hy-droxylase, 4CL 4-coumaroyl-CoA-ligase, HCT hydroxycinnamoyl-CoA shikimate/quinate hydroxycinnamoyl transferase, C3H p-coumarate 3-hydroxylase, CCoAOMT caffeoyl-CoA O-methyltransferase, CCR cinnamoyl-CoA reductase, F5H ferulate 5-hydroxylase, COMT caffeic acid O-methyltransferase, and CAD cinnamyl alcohol dehydrogenase are comparable to those of other studies that applied this technique, e.g., Hradilová et al (2017), applied the MACE technique to pea with an output of 8 to 15 million reads per library, and 12.3-21.7 million reads per library were generated from the RNA of apple roots (Weiß et al 2017).…”
Section: Discussionmentioning
confidence: 74%
“…Significant changes in gene expression are marked with thicker lines. Enzyme names are abbreviated as follows: PAL phenylalanine ammonia-lyase, C4H cinnamate-4-hy-droxylase, 4CL 4-coumaroyl-CoA-ligase, HCT hydroxycinnamoyl-CoA shikimate/quinate hydroxycinnamoyl transferase, C3H p-coumarate 3-hydroxylase, CCoAOMT caffeoyl-CoA O-methyltransferase, CCR cinnamoyl-CoA reductase, F5H ferulate 5-hydroxylase, COMT caffeic acid O-methyltransferase, and CAD cinnamyl alcohol dehydrogenase are comparable to those of other studies that applied this technique, e.g., Hradilová et al (2017), applied the MACE technique to pea with an output of 8 to 15 million reads per library, and 12.3-21.7 million reads per library were generated from the RNA of apple roots (Weiß et al 2017).…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, we have shown that the pod shattering phenotype depends not only on the single effects of the genes, but also on their epistatic interactions. We also discuss our findings for P. vulgaris in comparison with V. unguiculata (Suanum et al ., ; Lo et al ., ), G. max (Dong et al ., ; Funatsuki et al ., ), M. truncatula (Fourquin et al ., ; Ferrándiz and Fourquin, ) and P. sativum (Hradilová et al ., ), to shed light on the genetic mechanisms of convergent evolution under parallel selection and domestication.…”
Section: Discussionmentioning
confidence: 99%
“…Hradilová et al . () suggested that in P. sativum the main candidate gene responsible for pod shattering and localized on linkage group III is a homolog of peptidoglycan‐binding domain protein (PGDB) of Medicago truncatula . These proteins might have a general peptidoglycan‐binding function, and this motif is found at the N‐ or C‐terminus of a variety of enzymes involved in bacterial cell‐wall degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The β-1,3-Glucanase (EC 3.2.1.39) plays roles in the regulation of seed germination, dormancy, and in the defense against pathogens. The β-1,3-glucan layer is in the seed coat of cucurbitaceous species and confers seed semi-permeability [64]. In tobacco seeds, β-1,3-Glucanase was shown to be at the micropylar part of the endosperm prior to radicle protrusion, and seems to play a role in cell wall loosening [65].…”
Section: Genetic Basis Of Seed Dormancy Release In Legumesmentioning
confidence: 99%